Kegiatan Pengabdian melalui Penapisan Profil Gula Darah dalam Rangka Pencegahan Diabetes Melitus pada Populasi Lansia di Panti Werdha Hana - Alya Dwiana; Alexander Halim Santoso; Farell Christian Gunaidi; Ayleen Nathalie Jap; Daniel Goh (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease that is common in the elderly and has a major impact on quality of life, especially through risk complications such as impaired vision, heart disease, kidney failure, and amputation. The elderly are often unaware of the early symptoms of diabetes because complaints are considered part of the aging process, such as fatigue or frequent urination. The Community Service Program (PKM) at Panti Werdha Hana aims to increase awareness of the elderly about the importance of early detection of diabetes through fasting blood sugar screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach which includes checking blood sugar levels with the Point-of-Care Testing (POCT) tool and educational counseling on risk factors and prevention of diabetes. The results showed that out of 76 participants, 8 people (10.53%) were identified as having diabetes, 9 people (11.84%) had prediabetes, and the rest had normal blood sugar levels. Early detection through screening has proven to be an important step in preventing diabetes progression and severe complications, as well as supporting the improvement of the quality of life of the elderly through timely interventions and ongoing education.